Optogenetic elevation of endogenous glucocorticoid level in larval zebrafish - De Marco, Rodrigo J.; Groneberg, Antonia H.; Yeh, Chen-Min; Castillo Ramírez, Luis A.; Ryu, Soojin (Frontiers in Neural Circuits, 2013)
The stress response is a suite of physiological and behavioral processes that help to maintain or reestablish homeostasis. The hypothalamic-pituitary-adrenal (HPA) axis is central to the stress response, as it releases crucial hormones in response to stress. Glucocorticoids (GCs) are the final effector hormones of the HPA axis and exert a variety of actions under both basal and stress conditions. Despite their far-reaching importance for health, specific GC effects have been difficult to pin-down due to a lack of methods for selectively manipulating endogenous GC levels. To study stress-induced GC effects, we developed a novel optogenetic approach to selectively manipulate the rise of GCs triggered by stress. Using this approach, we could induce both transient hypercortisolic states and persistent forms of hypercortisolaemia in freely behaving larval zebrafish. Our results also established that transient hypercortisolism leads to enhanced locomotion shortly after stressor exposure. Altogether, we present a highly specific method for manipulating the gain of the stress axis with high temporal accuracy, thereby altering endocrine and behavioral responses to stress as well as basal GC levels. Our study thus offers a powerful tool for the analysis of rapid (non-genomic) and delayed (genomic) GC effects on brain function and behavior, feedbacks within the stress axis and developmental programming by GCs.